2019
DOI: 10.2174/0929867325666180713125314
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides: Amphibian Host Defense Peptides

Abstract: Antimicrobial peptides (AMPs) are one of the most common components of the innate immune system that protect multicellular organisms against microbial invasion. The vast majority of AMPs are isolated from the frog skin. Anuran (frogs and toads) skin contains abundant AMPs that can be developed therapeutically. Such peptides are a unique but diverse group of molecules. In general, more than 50% of the amino acid residues form the hydrophobic part of the molecule. Normally, there are no conserved structural moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 149 publications
0
76
0
Order By: Relevance
“…In T. molitor , the identified AMPs include tenecins (-1, -2, -3, -4) [ 48 , 49 , 50 ], attacins [ 51 ], defensins [ 52 ], and coleopterins [ 53 ]. In general, AMPs are known to act against Gram-positive and -negative bacteria and fungi [ 48 , 54 , 55 ] by membrane disruption, interference with bacterial metabolism, and targeting of cytoplasmic components [ 47 , 56 , 57 ]. Therefore, based on our in vitro results, it could be suggested that biosurfactants induce the production of active AMPs against E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…In T. molitor , the identified AMPs include tenecins (-1, -2, -3, -4) [ 48 , 49 , 50 ], attacins [ 51 ], defensins [ 52 ], and coleopterins [ 53 ]. In general, AMPs are known to act against Gram-positive and -negative bacteria and fungi [ 48 , 54 , 55 ] by membrane disruption, interference with bacterial metabolism, and targeting of cytoplasmic components [ 47 , 56 , 57 ]. Therefore, based on our in vitro results, it could be suggested that biosurfactants induce the production of active AMPs against E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…They have a promising capacity in the therapeutic and prophylactic applications [ 4 , 5 ]. Moreover, AMP-derived drugs are administered as topical formulations to treat skin and wound infections [ 6 ]. Some AMPs also show anticancer effects or have anticancer properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several frog species produce peptides with broad-spectrum antibacterial and antifungal activities that are also able to disrupt the plasma membrane of mammalian cells and more than 1000 such peptides have been described (reviewed in [ 6 , 7 , 8 , 9 , 10 , 11 ]). Although their precise biological role is incompletely understood, these peptides probably function as a component of the animal’s system of innate immunity, playing a role in the first-line defense against invading pathogens [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%